Regular Practice of Autogenic Training Reduces Migraine Frequency and Is Associated With Brain Activity Changes in Response to Fearful Visual Stimuli - Dobos, Dóra; Szabó, Edina; Baksa, Dániel; Gecse, Kinga; Kocsel, Natália; Pap, Dorottya; Zsombók, Terézia; Kozák, Lajos R.; Kökönyei, Gyöngyi; Juhász, Gabriella (Frontiers in Behavioral Neuroscience, 2022)
Several factors can contribute to the development and chronification of migraines, including stress, which is undoubtedly a major trigger. Beyond pharmacotherapy, other treatment methods also exist, including behavioral techniques aiming at reducing patients' stress response. However, the exact brain mechanisms underlying the efficacy of such methods are poorly understood. Our pilot study examined whether regular practice of autogenic training induces functional brain changes and if so, how it could be associated with the improvement of migraine parameters. By exploring neural changes through which autogenic training exerts its effect, we can get closer to the pathomechanism of migraine. In particular, we investigated the effect of a headache-specific autogenic training on brain activation using an implicit face emotion processing fMRI task in female healthy and episodic migraine subjects. Our focus was on migraine- and psychological stress-related brain regions. After a 16-week training course, migraineurs showed decreased activation in the migraine-associated dorsal pons to fearful compared to neutral visual stimuli. We also detected decreasing differences in supplementary motor area activation to fearful stimuli, and in posterior insula activation to happy stimuli between healthy subjects and migraineurs. Furthermore, migraineurs reported significantly less migraine attacks. These brain activation changes suggest that autogenic training may influence the activity of brain regions responsible for emotion perception, emotional and motor response integration, as well as cognitive control, while also being able to diminish the activation of regions that have an active role in migraine attacks. Improvements induced by the training and the underlying neurophysiological mechanisms are additional arguments in favor of evidence-based personalized behavioral therapies.